Immunogenicity, Tolerability and Safety in Adolescents of Bivalent rLP2086, a Meningococcal Serogroup B Vaccine, Coadministered with Quadrivalent Human Papilloma Virus Vaccine. Issue 5 (May 2016) - Senders, Shelly; Bhuyan, Prakash; Jiang, Qin; Absalon, Judith; Eiden, Joseph J.; Jones, Thomas R.; York, Laura J.; Jansen, Kathrin U.; O'Neill, Robert E.; Harris, Shannon L.; Ginis, John; Perez, John L.
Abstract : Background: This study in healthy adolescents (11 to <18 years) evaluated coadministration of quadrivalent human papillomavirus vaccine (HPV-4), with bivalent rLP2086, a meningococcal serogroup B (MnB) vaccine. Methods: Subjects received bivalent rLP2086 + HPV-4, bivalent rLP2086 + saline or saline + HPV-4 at 0, 2 and 6 months. Immune responses to HPV-4 antigens were assessed 1 month after doses 2 and 3. Serum bactericidal assays using human complement (hSBAs) with 4 MnB test strains expressing vaccine-heterologous human complement factor H binding protein (fHBP) variants determined immune responses to bivalent rLP2086. Coprimary objectives were to demonstrate noninferior immune responses with concomitant administration compared with either vaccine alone. Additional endpoints included the proportions of subjects achieving prespecified protective hSBA titers to all 4 MnB test strains (composite response) and ≥4-fold increases in hSBA titer from baseline for each test strain after dose 3; these endpoints served as the basis of licensure of bivalent rLP2086 in the US. Results: The noninferiority criteria were met for all MnB test strains and HPV antigens except HPV-18; ≥99% of subjects seroconverted for all 4 HPV antigens. Bivalent rLP2086 elicited a composite response in >80% of subjects and increased hSBA titers ≥4-fold in ≥77% of subjects for each test strain after dose 3. A substantial bactericidal response was also observed in a large proportion of subjects after dose 2. Local reactions and systemic events did not increase with concomitant administration. Conclusions: Concomitant administration of bivalent rLP2086 and HPV-4 elicits robust immune responses to both vaccines without increasing reactogenicity compared with bivalent rLP2086 alone. Concurrent administration may increase compliance with both vaccine schedules. Abstract : Supplemental Digital Content is available in the text.